Cyclic oxygen exchange capacity of Ce-doped V2O5 materials for syngas production via high-temperature thermochemical-looping reforming of methane. Issue 37 (1st July 2021) - Riaz, Asim; Lipiński, Wojciech; Lowe, Adrian
Abstract : Cerium doping into the V2 O5 lattice forms a reversible V2 O3 /VO redox pair after sequential methane partial oxidation and CO2 /H2 O splitting reactions and produces syngas (H2, CO) with fast rates and high oxygen exchange capacity. Abstract : Synthesis gas production via solar thermochemical reduction-oxidation reactions is a promising pathway towards sustainable carbon-neutral fuels. The redox capability of oxygen carriers with considerable thermal and chemical stability is highly desirable. In this study, we report Ce-doped V2 O5 structures for high-temperature thermochemical-looping reforming of methane coupled to H2 O and CO2 splitting reactions. Incorporation of fractional amounts of large cerium cations induces a V 5+ to V 3+ transition and partially forms a segregated CeVO4 phase. More importantly, the effective combination of efficient ion mobility of cerium and high oxygen exchange capacity of vanadia achieves synergic and cyclable redox performance during the thermochemical reactions, whereas the pure vanadia powders undergo melting and show non-cyclic redox behaviour. These materials achieve noteworthy syngas production rates of up to 500 mmol molV −1 min −1 during the long-term stability test of 100 CO2 splitting cycles. Interestingly, the cerium ions are mobile between the lattice and the surface of the Ce-doped vanadia powders during the repeated reduction and oxidation reactions and contribute towards the cyclic syngas production. However, this also causes the formation of the CeVO4 phase in Ce-rich powders, which increases the H2 /CO ratios and lowers fuel selectivity, which can be controlled by optimizing the cerium concentration. These findings are noteworthy towards the experimental approach of evaluating the oxygen carriers with the help of advanced characterization techniques.